Quality Improvement Project: RCPsych Portfolio Training for Psychiatry Trainees at East London NHS Foundation Trust - Keerthi Vijayan; Kristen Hindley; Sen Kallumpuram; Aneeba Anwar; Natalie Ashburner (BJPsych Open)
Aims: A questionnaire distributed to psychiatry trainees at the East London NHS Foundation Trust ascertained that, as of July 2024, trainees had not received formal training on navigating the Portfolio Online system. Additionally, there was no easily accessible document outlining key information for understanding the portfolio and the Annual Review of Competency Progression (ARCP) requirements.